2013
DOI: 10.1124/dmd.113.052753
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin as an In Vivo Probe for Studying Hepatic Organic Anion Transporting Polypeptide-Mediated Drug–Drug Interactions in Cynomolgus Monkeys

Abstract: Drug-drug interactions (DDIs) caused by the inhibition of hepatic uptake transporters such as organic anion transporting polypeptide (OATP) can affect therapeutic efficacy and cause adverse reactions. We investigated the potential utility of pitavastatin as an in vivo probe substrate for preclinically studying OATP-mediated DDIs using cynomolgus monkeys. Cyclosporine A (CsA) and rifampicin (RIF), typical OATP inhibitors, inhibited active uptake of pitavastatin into monkey hepatocytes with half-maximal inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 31 publications
4
47
0
Order By: Relevance
“…Recently, an increasing number of investigators have used the cynomolgus monkey as a model to study the inhibition of drug transporters in vivo (Tahara et al, 2006;Shen et al, 2013Shen et al, , 2015bTakahashi et al, 2013;Uchida et al, 2014;Chu et al, 2015;Karibe et al, 2015). Such a model offers advantages in drug development, when the transporter inhibition potential of a clinical candidate requires more extensive evaluation of changes in victim drug pharmacokinetics and organ toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an increasing number of investigators have used the cynomolgus monkey as a model to study the inhibition of drug transporters in vivo (Tahara et al, 2006;Shen et al, 2013Shen et al, , 2015bTakahashi et al, 2013;Uchida et al, 2014;Chu et al, 2015;Karibe et al, 2015). Such a model offers advantages in drug development, when the transporter inhibition potential of a clinical candidate requires more extensive evaluation of changes in victim drug pharmacokinetics and organ toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Both cOATP1B1 and cOATP1B3 are functionally similar to their human orthologs, both in terms of in vitro transport activity and inhibition potency with selected substrates and inhibitors tested (Shen et al, 2013). Importantly, in vivo DDIs of rosuvastatin (RSV) and pitavastatin with rifampin (RIF), a potent inhibitor of OATP1B, have been reported in cynomolgus monkeys (Shen et al, 2013;Takahashi et al, 2013). It is therefore conceivable that cynomolgus monkeys could be an appropriate preclinical model to identify endogenous biomarkers that are also sensitive to OATP1B inhibition in humans.…”
Section: Introductionmentioning
confidence: 99%
“…and PO administration of the statins tested, respectively, to ensure that the RIF concentrations reached a maximum level at early time points after i.v. and PO dosing of RSV or ATV (Shen et al, 2013;Takahashi et al, 2013). The animals were divided into various treatment groups with four animals in each group: RIF PO, RSV or ATV i.v., RSV or ATV PO, RSV or ATV i.v.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cynomolgus monkey OATPs (cOATPs) share a high degree of amino acid sequence identity and functional similarity to their human counterparts (Shen et al, 2013;Takahashi et al, 2013). Concomitant with these identities and similarities, there are investigations employing the cynomolgus monkey as an in vivo preclinical model to assess OATP DDIs (Shen et al, 2013;Takahashi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant with these identities and similarities, there are investigations employing the cynomolgus monkey as an in vivo preclinical model to assess OATP DDIs (Shen et al, 2013;Takahashi et al, 2013). The DDIs have been investigated in other animal models; however, the sequences and transporting profiles obtained for xenobiotics in other animal species are frequently different from those obtained in humans, reducing the utility of such animals (Shitara et al, 2003;Shirasaka et al, 2010;Li et al, 2013).…”
Section: Introductionmentioning
confidence: 99%